Eating disorders and substance use at a South African tertiary hospital over a 21-year period - Hannelie Williams; Karis Moxley; Muiruri Macharia; Martin Kidd; Gerhard P. Jordaan (South African Journal of Psychiatry, 2020)
Background: Eating disorders (EDs) and substance-related disorders pose a challenge when they co-occur and have implications for patient management. Clinical information on EDs and substance-related disorders as independent disorders is fairly well established in South Africa, but our understanding of the coexistence of these disorders is limited.